A facile synthesis of a highly stable superhydrophobic nanofibrous film for effective oil/water separation. Issue 85 (31st August 2016) - Kong, Xian; Zhang, Junming; Liao, Xuepin; Huang, Xin; Shi, Bi
Abstract : An oil/water separation film with excellent durability and stable recyclability is highly desired for the treatment of oil containing effluents, like industrial oily wastewater. Abstract : An oil/water separation film with excellent durability and stable recyclability is highly desired for the treatment of oil containing effluents, like industrial oily wastewater. Herein, a novel superhydrophobic nanofibrous film (SNF) was fabricated by growing TiO2 on a collagen fiber membrane (CFM), followed by surface coating of vinyl triethoxysilane. The as-prepared SNF was well characterized by SEM, SEM-EDS and XPS. Due to the unique structure, the SNF featured superhydrophobicity with a water contact angle (WCA) of 153°. When applied in the separation of oil/water mixtures, SNF exhibited a high separation efficiency of ∼97% in 5 circles, and it showed more effective oil/water separation efficiency compared to the commercial PTFE film. SNF was also effective for the separation of gasoline/water or diesel oil/water mixtures with varied volume ratios, and all the corresponding separation efficiencies were higher than 97% even after 5 cycles. In addition, SNF could still maintain superhydrophobicity with WCA around 150° after being treated by high temperature (120 °C), ultraviolet irradiation, water or organic solvent immersion for 24 h, manifesting an excellent durability.